‘Coi libri o col mondo?’: Effetti di straniamento e spaesamento mancato nel "Viaggio e maravigliose avventure" di Francesco Contarini - Del Buono, Bianca (Incontri. Rivista europea di studi italiani, 2021)
‘With books or with the world?’ Alienation effects without disorientation in Viaggio e maravigliose avventure d’un veneziano by Francesco Contarini This paper investigates the forms and effects of displacement in Viaggio e maravigliose avventure d’un veneziano ch’esce per la prima volta dalle lagune e si reca a Padova e a Milano, published anonymously in Milan in 1818. According to Luigi Catucci, the author is Francesco Contarini, who translated many travel books for the editor Sonzogno between 1816 and 1817: this would explain the noticeable intertextual dialogue between the Viaggio and other travel writings, both fictional and non-fictional. Some allusions to Vasco de Gama’s and James Cook’s geographical explorations reveal the author’s interest in travel as an anthropological experience, while quotations from Swift and De Maistre suggest a familiarity with the literary conventions and the most recent renewal of the European novel. From a theoretical point of view, the essay examines the interaction between travel literature, (anti-)novel, récit excentrique, and parody, in order to show that literary contamination works as an estrangement device. At the same time, this theoretical interpretation is evaluated (from an analytical and interpretative point of view) in relation to the narrative techniques through which Contarini expresses the alienation-effect of the first-person dramatized narrator, prompting a strong sense of disorientation in the reader (but not in the main character).